Cytogenetic analysis in prenatal diagnosis. - Schonberg, S A (1993)
Chromosome analysis is the single most frequent test used in laboratory prenatal diagnostic studies. I summarize the current status of the field, including diagnostic problems in the laboratory and the clinical problems associated with communicating unexpected laboratory findings. I explore the effect of molecular genetics on these issues and its possible future effects on the entire practice of prenatal diagnosis as it relates to the risk for chromosome nondisjunction (trisomy). I also discuss the use of cytogenetic analysis in the prenatal diagnosis of certain inherited genetic diseases.